Extracción de diente ectópico en comunicación con piso de cavidad nasal: reporte de caso (2020)
Ectopic tooth eruption is a rare occurrence to witness during a dental consultation. This anomaly is generally asymptomatic and frequently discovered only by radiographs taken during a routine dental check-up, however, it can be followed by pathological processes such as cysts, bone resorption, or infection, among others. The aim of this text is to present the clinical management and treatment of a maxillary tooth in an ectopic position in communication with the right nasal cavity. This is a report of the clinical case of a 45-year-old female patient who seeks dental attention during a health brigade, located in a rural place in Colombia, reporting symptoms of pain on the roof of the mouth and a history of epistaxis. Upon clinical examination, she presented a soft, fluctuating lesion on the palate with slight drainage of purulent material. The presence of an ectopic tooth is discovered through exploratory surgery, and the tooth is extracted. Constant follow-up is carried out for four months, and the patient shows a satisfactory recovery, reporting total relief of symptoms; all this despite the limitations generated by the socioeconomic level of the patient and the environment in which the dental care is carried out. Correctly diagnosing dental anomalies is of utmost importance in order to provide an adequate and timely treatment.